Oxford International primary English student book 4 - Danihel, Emma; Hearn, Izabella (Karachi Oxford University Press, 2022)
The Oxford International Primary English Workbook 4 for the Pakistan edition complements the Student Book with practical exercises to reinforce English language skills. It focuses on improving reading, writing, grammar, and vocabulary through engaging activities and worksheets. The workbook offers a variety of exercises such as fill-in-the-blanks, sentence formation, and comprehension questions, all designed to support and extend the lessons from the Student Book. It aims to provide students with hands-on practice to enhance their understanding and application of English in an enjoyable and effective manner.
Keywords: English -Text Book